The Influence of Application Government Internal Control System, Asset Management and Human Resources Competencies to Financial Accountability - Sabrina Nur Fhadillah; Ivan Yudianto (Journal of Accounting Auditing and Business, 2018)
TThis research aims to examine the influence of the application of government internal control system, asset management, and human resources competencies toward financial accountability of Bandung Municipal Government. Survey research was conducted in 27 Local Work Unit of Bandung Municipal. This research using the descriptive-quantitative method by spreading a questionnaire to every Local Work Unit as much as 55 questionnaires. The respondent of this research is an auditor, staff of finance, and asset management. Method of data analysis used by this research is multiple linear regression that assisted with SPSS software. The result of this research showed that: (1) The application of Government Internal Control System significantly influence financial accountability of Bandung Municipal Government with 0,016640 percentage or 1,166%; (2) Asset management significantly influence financial accountability of Bandung Municipal Government with 0,423200 percentage or 42,32%; (3) The human resource competencies significantly influence financial accountability of Bandung Municipal Government with 0,356208 percentage or 35,62%. Also, the simultaneous influence of government internal control system, asset management, and human resources competencies to financial accountability are 79.6%, and amount of the rest is 20,4% affected by another factor outside of this research. In Local Work Unit, Bandung municipal still need supervision about accountability and recording to local asset and improve commitment leader. With the expected improvements in the government's financial statements, the financial statements of Bandung municipal could be better in 2017.